2021
DOI: 10.3146/ps21-2.1
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Evaluation of Nozzle Types for Peanut Pest Management Using Commercial Sprayers

Abstract: Growers have rapidly adopted auxin-resistant cotton and soybean technologies. In Georgia, growers who plant auxin-resistant cotton/soybean are required to utilize nozzles that produce larger (coarser) droplets when spraying auxin herbicides to minimize potential off-target movement of pesticides. Consequently, these nozzles are also used in peanut (an important rotational crop with cotton) since changing nozzles between crops is uncommon for growers. However, larger droplets can result in reduced spray coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…However, with the exception of chlorothalonil, fungicides used in the present study were systemic, and nozzle selection most likely less critical. A more detailed study with herbicides and fungicides representing all modes of action and/ or systemic movement with the nozzles used in our study would be informative, especially in North Carolina to corroborate or refute the findings of Virk et al [7]. Depending on constraints growers may have in their communities, application using nozzles that deliver large droplets is an effective practice to avoid particle drift.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, with the exception of chlorothalonil, fungicides used in the present study were systemic, and nozzle selection most likely less critical. A more detailed study with herbicides and fungicides representing all modes of action and/ or systemic movement with the nozzles used in our study would be informative, especially in North Carolina to corroborate or refute the findings of Virk et al [7]. Depending on constraints growers may have in their communities, application using nozzles that deliver large droplets is an effective practice to avoid particle drift.…”
Section: Discussionsupporting
confidence: 65%
“…This phenomenon would make coverage of foliage less critical for these fungicides (e.g., azoxystrobin, prothioconazole plus tebuconazole, and pyraclostrobin) while coverage is more important for contact fungicides that are not readily absorbed and forms a layer of protection from pathogens on the leaf surface (e.g., chlorothalonil). Virk et al [7] reported that disease control, including late leaf spot, did not differ when fungicides were applied with range of nozzles similar to the range used in our experiment. Similar to our findings, weed control with herbicides was not affected by nozzle selection over the cropping cycle.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Higher ground speeds have been shown to lead to a heightened generation of smaller droplets, consequently raising the risk of spray drift. Several studies have documented greater pesticide drift and reduced coverage associated with increases in the travel speed of the tractor [6][7][8][9][10]. In addition, resistance to pests can develop over time, which impairs the effectiveness of pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Among the main pests that occur in peanuts, the lepidopterous genera Stegasta , Spodoptera , Chrysodeixis and Helicoverpa are the most important ( Michelotto et al., 2012 ; Pinto et al., 2020 ; Virk et al., 2021 ; Costa et al., 2022 ). In addition to lepidoptera, the peanut crop is severely attacked by thrips, especially the honeysuckle thrips Enneothrips flavens Molton ( Lourenção et al., 2007 ; Calore et al., 2012 ; Michelotto et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%